The paths of Public Governance (Research, Society and Development, 2022)
The objective of this research is to carry out a literary overview about Governance, with the perspective of elaborating a historical, conceptual panel, of theoretical elements and highlighting the itinerary that resulted in Public Governance and its Electronic version, in order to, in this way, qualify it properly. As a methodological resource, bibliographical research and systematic reading review are used. It was found that the constitution of Public Governance resulted from the alternation of administrative models, from Public Administration to New Public Management, and from dysfunctionalities pointed out for the latter. As an offshoot of Public Governance, Electronic Governance incorporates its fundamentals, such as dialogue with society and the focus of government actions on the citizen, and combines the use of electronic communication tools based on the Internet to offer services with greater agility, transparency and efficiency, this for larger portions of the population. 16 types of Governance were cataloged and described (such as Community, Corporate and Participatory) and more than 30 characteristics of Public Governance (such as openness, equality and legitimacy), which can be used as subsidies to better detail this movement, as well as in investigations that want to raise its essential properties.